2022
DOI: 10.1186/s13046-022-02556-2
|View full text |Cite
|
Sign up to set email alerts
|

A reciprocal feedback between colon cancer cells and Schwann cells promotes the proliferation and metastasis of colon cancer

Abstract: Background Research has indicated that the emergence of Schwann cells around premalignant lesions of colon cancer might be an early indicator promoting the onset of tumorigenesis. The present study explored the communication between colon cancer cells and Schwann cells. Methods Immunofluorescence analyses were conducted to examine the differential distribution of Schwann cells within colon cancer tissues and normal colon tissues. CCK8 assay, colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Studies have shown elevated NGF expression in oral cancer tissues compared to healthy mucosa. Higher NGF levels have also been associated with increased proliferation and migration in oral cancer cell lines.In pancreatic cancer,NGF could encourage the neuroinvasive potential of pancreatic cancer cells [34] ,and treatment targeting nerve growth factor (NGF) and autophagy pathways may inhibit peripheral nerve in ltration and provide new research directions and an experimental basis for understanding and treating this process [35] . A study [36] initially examinied the low-glucose environment of oral mucosa carcinomas, we discovered that cancer cells employ ROS-triggered activation of c-Jun to secrete NGF, which conditions nociceptive nerves for calcitonin gene-related peptide (CGRP)…”
Section: Evaluation Of the Effect Of Oral Cancer Risk On In Ammatory ...mentioning
confidence: 99%
“…Studies have shown elevated NGF expression in oral cancer tissues compared to healthy mucosa. Higher NGF levels have also been associated with increased proliferation and migration in oral cancer cell lines.In pancreatic cancer,NGF could encourage the neuroinvasive potential of pancreatic cancer cells [34] ,and treatment targeting nerve growth factor (NGF) and autophagy pathways may inhibit peripheral nerve in ltration and provide new research directions and an experimental basis for understanding and treating this process [35] . A study [36] initially examinied the low-glucose environment of oral mucosa carcinomas, we discovered that cancer cells employ ROS-triggered activation of c-Jun to secrete NGF, which conditions nociceptive nerves for calcitonin gene-related peptide (CGRP)…”
Section: Evaluation Of the Effect Of Oral Cancer Risk On In Ammatory ...mentioning
confidence: 99%
“…Transwell assay was conducted to assess the migration and invasion capacities of HCT116 cells [32]. Following drug pretreatment, the cells (1 × 10 5 cells/well) were resuspended in 200 µL of DMEM without serum and then positioned in the upper chamber.…”
Section: Transwell Migration and Invasion Assaymentioning
confidence: 99%
“…In xenograft mouse models of TNBC, treatment with anthracycline was evidenced to increase sympathetic nerve fiber activity and norepinephrine concentration in mammary tumors through the induction of nerve growth factor (NGF) by tumor cells, thus driving metastasis [ 322 ]. Cancer exosomes have been demonstrated to induce tumor innervation [ 323 ], and a reciprocal feedback between colon cancer cells and schwann cells mediated by exosomes were also reported to promote the proliferation and metastasis of colon cancer [ 324 ]. More recently, neurotransmitter gamma-amino butyric acid (GABA) induced by sleep deprivation was shown to promote the metastasis of colon cancer through miR‑223‑3p endogenous pathway and exosome pathway [ 325 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%